2005
DOI: 10.1086/431259
|View full text |Cite
|
Sign up to set email alerts
|

Fertility, Child Work, and Schooling Consequences of Family Planning Programs: Evidence from an Experiment in Rural Bangladesh

Abstract: Despite the attractiveness of experiments from the perspective of program evaluation, there have been very few program experiments in the area of family planning. This paper evaluates an ongoing family planning program experiment in rural Bangladesh. The paper estimates the effect of mothers' program exposure on fertility and children's time allocation. The results show that while the program was effective in reducing fertility, it had no significant impact on children's school enrollment. However, the program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…However, these family composition and birth timing variables are excluded here as controls, because they may be affected by family choices, and hence are potentially correlated with mortality and 14 fertility for other reasons or endogenous to these family outcomes (Koenig et al 1990Faveau et al 191;Muhuri and Preston 1991;Muhuri 1995;Muhuri and Menken 1997;Foster and Roy 2000;Sinha, 2005).…”
Section: Impacts On Fertility and Mortalitymentioning
confidence: 99%
“…However, these family composition and birth timing variables are excluded here as controls, because they may be affected by family choices, and hence are potentially correlated with mortality and 14 fertility for other reasons or endogenous to these family outcomes (Koenig et al 1990Faveau et al 191;Muhuri and Preston 1991;Muhuri 1995;Muhuri and Menken 1997;Foster and Roy 2000;Sinha, 2005).…”
Section: Impacts On Fertility and Mortalitymentioning
confidence: 99%
“…Although it is difficult to validly compare results across studies, this estimated 3 per cent lower completed fertility is below the 10 per cent reported for Colombia (Miller, 2010) and the 13-17 per cent for Bangladesh (Sinha, 2005;Joshi & Schultz, 2013). Our estimated six percentage points effect of presence of the NFPP in a community on the probability of having had contraceptive experience for women aged 35-39, however, is rather similar to the five to six percentage points increase in contraceptive prevalence reported by Entwisle et al (1984) for Thai women living close to a family planning outlet.…”
Section: Predictionsmentioning
confidence: 72%
“…This increased contraceptive use explains 75 per cent of the fertility decline in Indonesia over the [1982][1983][1984][1985][1986][1987] period. The results of Gertler and Molyneaux (1994) may explain that the studies referred to above of Hermalin and Khar (1996), Miller (2010), and Sinha (2005) find small impacts of family planning programs on fertility. In Thailand, however, early research seems to suggest that the 1976 introduction of a free pill policy did lead to an increase in pill users (Knodel, Bennett, & Panyadilok, 1984), while living closer to a family planning outlet increased contraceptive prevalence by about five to eight percentage points (Entwisle, Hermalin, Kamnuansilpa, & Chamratrithirong, 1984).…”
Section: Introductionmentioning
confidence: 79%
“…For one such intervention -early childhood programs in Jamaica (Walker et al 2005) -the authors were able to give us cost information. Unfortunately, no cost information was available for the following six studies by Sinha (2005), Bedi & Marshall (2002), Case and Deaton (1999), Dreze and Kingdon (2000), Lloyd et al (2005), and Zimmerman (2003) -either from authors or from other sources recommended by the authors. Therefore, these studies were dropped from the subsequent cost-effectiveness analysis, even though (for completeness) we mention the findings from these papers in the next section.…”
Section: (C) Cost Of Interventionsmentioning
confidence: 99%